Effects of Saharan Dust Advection on Atmospheric Aerosol Properties in the West-Mediterranean Area. (21st May 2012) - Pavese, G.; Calvello, M.; Esposito, F.; Leone, L.; Restieri, R.
Abstract : Eight measurement campaigns for the characterization of atmospheric aerosol properties were conducted from 2001 until 2008 at five sites located in the Western Mediterranean basin. Radiometric measurements were used to obtain Aerosol Optical Depth, Ångström parameters, and aerosol size distributions, allowing differentiation of background conditions from anthropogenic, marine, or Saharan dust aerosol advection. The analysis was focused on the study of optical and physical properties variation of atmospheric aerosols under Saharan outbreaks. Dust-affected data were analysed all together, independently from the measurements site, thus allowing the highlighting of similarities and differences among them. The scatter-plot Ångström exponent versus AOD at 780 nm shows a correlation among all dust data, while an overlapping region with no-dust data reveals the simultaneous presence of mineral, anthropogenic, and marine particles. Daily averaged volume size distributions can be unimodal or bimodal functions and one three-modal distribution, with a coarse mode generally prevailing. Finally, considering the ratio of small/large particles n s / n l and plotting the corresponding histogram for all dust data, a sharp frequency distribution is obtained with 89% of data in the range 5–65, while 89% of no-dust data extend from 5 to 135, in spite of different sources, pathways, and arrival sites.